2017
DOI: 10.1007/s00464-017-5663-1
|View full text |Cite
|
Sign up to set email alerts
|

Passing the fundamentals of endoscopic surgery (FES) exam: linking specialty choice and attitudes about endoscopic surgery to success

Abstract: These data support existing research suggesting that current flexible endoscopy training in residency may be insufficient for trainees to pass the FES examination, and that failure rates hold true even for this select group of trainees who have chosen a profession in GI surgery and intend to use endoscopy in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…1 However, recent studies have shown that clinical endoscopy experience alone may not be sufficient preparation for trainees to pass this examination. 3 4 In this vein, several institutions developed their own proficiency-based simulation curricula to train for the skills component of the FES examination. 5 6 7 These curricula have utilized physical 5 7 and/or VR simulators 6 for training.…”
mentioning
confidence: 99%
“…1 However, recent studies have shown that clinical endoscopy experience alone may not be sufficient preparation for trainees to pass this examination. 3 4 In this vein, several institutions developed their own proficiency-based simulation curricula to train for the skills component of the FES examination. 5 6 7 These curricula have utilized physical 5 7 and/or VR simulators 6 for training.…”
mentioning
confidence: 99%
“…written examination and a hands-on skill test on a simulator (12). Unsatisfactory pass-rates on the hands-on skill tests have led to the creation of simulation training systems and curricula (13). Selfpractice represents a major part of the preparation before the trainee is ready to take the examinations, and our study represents a method to optimize the time spent when novices engage the initial steps of learning a colonoscopy, the progression from anus to cecum.…”
Section: Resultsmentioning
confidence: 99%